Concentration and time of feeding with 17-α-methyltestosterone oil diluted and incorporated to the feed for masculinization of Nile tilapia - Ota, Érika do Carmo; Inoue, Luís Antônio Kioshi Aoki; Silva, Tarcila Souza de Castro (Acta Scientiarum. Animal Sciences, 2023)
Tilapia masculinization can be induced by oral administration of α-methyltestosterone (MT), which is commonly dissolved in ethanol to be added to the feed. However, there are many benefits in using alternative vehicles, such as oil. The incorporation time, vehicles quantity, safety for handlers, fish and the environment are favorable factors. In fry fed for 35 days under temperature control, we found that masculinization rate was similar in both incorporation vehicles of MT (oil or ethanol) in the concentrations studied (30 and 60 mg MT kg-1 feed). In an experiment, using hormone oil dissolution and oral administration at 30 mg MT kg-1 feed, it was observed that the longer the administration time, the lower the coefficient of variation in the masculinization rate. Therefore, administration for 32 days showed the lowest variability in the masculinization rate (99.8 ± 0.5 %), compared to 24 (98.5 ± 3.0 %), 16 (97.0 ± 6.0 %) and 8 (89.0 ± 8.8 %) days. The field experiment confirmed the results obtained in the lab. We concluded that the oil can be used as MT vehicle and we recommend to dispense it at the lowest hormonal concentration (30 mg MT kg-1 feed) for 32 days for tilapia masculinization.